Activation of the Chicken Anemia Virus Apoptin Protein by Chk1/2 Phosphorylation Is Required for Apoptotic Activity and Efficient Viral Replication - Kucharski, Thomas J. (J Virol, 2016)
Chicken anemia virus (CAV) is a single-stranded circular DNA virus that carries 3 genes, the most studied of which is the gene encoding VP3, also known as apoptin. This protein has been demonstrated to specifically kill transformed cells while leaving normal cells unharmed in a manner that is independent of p53 status. Although the mechanistic basis for this differential activity is unclear, it is evident that the subcellular localization of the protein is important for the difference. In normal cells, apoptin exists in filamentous networks in the cytoplasm, whereas in transformed cells, apoptin is present in the nucleus and appears as distinct foci. We have previously demonstrated that DNA damage signaling through the ataxia telangiectasia mutated (ATM) pathway induces the translocation of apoptin from the cytoplasm to the nucleus, where it induces apoptosis. We found that apoptin contains four checkpoint kinase consensus sites and that mutation of either threonine 56 or 61 to alanine restricts apoptin to the cytoplasm. Furthermore, treatment of tumor cells expressing apoptin with inhibitors of checkpoint kinase 1 (Chk1) and Chk2 causes apoptin to localize to the cytoplasm. Importantly, silencing of Chk2 rescues cancer cells from the cytotoxic effects of apoptin. Finally, treatment of virus-producing cells with Chk inhibitor protects them from virus-mediated toxicity and reduces the titer of progeny virus. Taken together, our results indicate that apoptin is a sensor of DNA damage signaling through the ATM-Chk2 pathway, which induces it to migrate to the nucleus during viral replication. IMPORTANCE The chicken anemia virus (CAV) protein apoptin is known to induce tumor cell-specific death when expressed. Therefore, understanding its regulation and mechanism of action could provide new insights into tumor cell biology. We have determined that checkpoint kinase 1 and 2 signaling is important for apoptin regulation and is a likely feature of both tumor cells and host cells producing virus progeny. Inhibition of checkpoint signaling prevents apoptin toxicity in tumor cells and attenuates CAV replication, suggesting it may be a future target for antiviral therapy.